Mucoadhesive capsules based on bacterial nanocellulose and chitosan as delivery system of turmeric extract - Laia Posada; Natalia Jaramillo-Quiceno; Cristina Castro; Marlon Osorio (Heliyon, 2023)
Current efforts in stomach-related drug design focus on improving drug bioavailability within the gastric region. Bacterial nanocellulose (BNC) has been established as a suitable material for drug delivery systems; however, it lacks adhesion to the gastric environment. This limitation can be addressed by leveraging the mucoadhesive properties of low molecular weight chitosan (LMWC). Therefore, we aimed to develop mucoadhesive capsules constructed from BNC coated with crosslinked LMWC, intended for targeted drug delivery in the gastric region. The capsules were characterized using scanning electron microscopy, infrared spectroscopy, thermogravimetric analysis, and mucoadhesion assessments. Under acidic conditions, crosslinked chitosan exhibited enhanced swelling relative to neutral conditions. The coating of chitosan onto the BNC fibrillar network of the capsules resulted in the superimposition of vibration bands and enhanced thermal stability. Furthermore, the capsules exhibited significant mucoadhesive properties in the gastric environment, with an attachment force measuring 89.151 ± 6.226 mN. To validate the efficacy of the system, we utilized antioxidant turmeric extract (TE) as a bioactive compound with chemopreventive potential against stomach cancer. TE was adsorbed onto BNC in a reversible multilayer system, enabling controlled adsorption and desorption. These findings highlight the significance of developing mucoadhesive capsules as a tailored drug delivery system for gastric conditions, particularly in the context of treating stomach diseases as cancer.